INTERNET SEHAT DAN AMAN (INSAN) - Donni Nasution; Elly Rahayu; Rohminatin Rohminatin (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2019)
Abstract: This service activity is carried out in the form of workshop where health and safe Internet became it's theme which was aimed to increasing the knowledge of women, especially the women of Bhayangkari Polsek Porsea in using the internet in a healthy and safe manner. The target audience of this Service Program are 20 women from bhayangkari Polsek Porsea. The method used are the lecture method, direct discussion and also question and answer. The material provided includes such as Women in the Technological Era, Empowering Women through Internet Technology, and also Healthy and Safe Internet. The benefits obtained from this service are the first is to improve current knowledge of technology for the women, the second is to increase the knowledge of the women roles in technology and the third is to educate the internet ethics and its benefits for herself and the family, children especially. Keywords: Insan, health and safe, Women, Internet  Abstrak: Kegiatan pengabdian ini  dilaksanakan dalam bentuk kegiatan Workhshop  yang bertemakan Internet sehat dan aman yang bertujuan meningkatkan pengetahuan perempuan khususnya ibu-ibu Bhayangkari dalam menggunakan internet secara sehat dan aman. Khalayak sasaran dalam kegiatan Pengabdian kepada Masyarakat ini adalah Ibu-Ibu bhayangkari yang berjumlah 20 orang. Metode yang digunakan adalah  metode ceramah, diskusi dan  tanya jawab secara langsung. Materi yang diberikan diantaranya  seperti Perempuan di Era Teknologi, Pemberdayaan Perempuan Melalui Teknologi Internet, serta Internet Sehat dan Aman. Manfaat yang diperoleh dari kegiatan pengabdian ini pertama meningkatkan pengetahuan. Teknologi masa kini kepada perempuan, kedua meningkkat pengetahuan tentang peran perempuan dalam Teknologi  dan ketiga melakukan edukasi etika berinternet serta manfaat  bagi  dirinya dan keluarga, terutama kepada anak-anak. Kata kunci: Insan, Sehat dan Aman, Wanita, Internet